2008
DOI: 10.1111/j.1708-8305.2008.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Delivery Risk in Migrants in Italy: An Observational Prospective Study

Abstract: In our setting, preterm delivery occurred more frequently in migrant women, particularly of African origin, and it is not associated to delayed access to antenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 11 publications
4
18
0
3
Order By: Relevance
“…No significant differences were found in the following outcome measures: maternal age, mode of delivery, average weight, length of hospital stay, Apgar score at 5 minutes, and RDS; however, there were more low birth weight infants (<2500 g) in the Argentine women population; these results are not consistent with the conclusions of the reviewed bibliography. [5][6][7] One of the causes described in the reviewed bibliography is that the rate of smoking native women is five times higher than, i.e., in the Bolivian population, 13 which may have contributed to the low birth weight of infants born from Argentine women. The higher prevalence of adolescent pregnancies among this population may also be related to the low birth weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences were found in the following outcome measures: maternal age, mode of delivery, average weight, length of hospital stay, Apgar score at 5 minutes, and RDS; however, there were more low birth weight infants (<2500 g) in the Argentine women population; these results are not consistent with the conclusions of the reviewed bibliography. [5][6][7] One of the causes described in the reviewed bibliography is that the rate of smoking native women is five times higher than, i.e., in the Bolivian population, 13 which may have contributed to the low birth weight of infants born from Argentine women. The higher prevalence of adolescent pregnancies among this population may also be related to the low birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…5 N u m e r o u s i n t e r n a t i o n a l investigations have demonstrated t h a t m i g r a n t p o p u l a t i o n s a r e vulnerable; and such vulnerability leads to complicated social and health difficulties that pose a strong challenge on health care services. In Italy it has been shown that the risk of preterm birth is significantly higher among migrants (p =0.015), 6 while in Spain the prevalence of adolescent pregnancies was 3-5 times higher among migrants compared to Spanish women. 7 Migrant women in Europe had a clear disadvantage in all outcome measures assessed: 43% of higher low birth weight risk, 24% of preterm delivery, 50% of perinatal mortality, and 61% of congenital malformations.…”
Section: Conflict Of Interest: Nonementioning
confidence: 98%
“…[5][6][7] Una de las causas descritas en la bibliografía consultada es que la proporción de mujeres nativas que fuman es cinco veces mayor que en la población boliviana, 13 hecho que podría contribuir al bajo peso al nacer en los hijos de madres nativas. La mayor prevalencia de embarazo adolescente en esta población podría corresponderse también con el bajo peso al nacer.…”
Section: Discussionunclassified
“…Their health indicators are frequently worse, which is explained by interactions between socio-material deprivation factors aggravated by stressors involved in the migration process. Along with issues related to health literacy concerning pregnancy and its assistance, migrants often obtain poorer medical follow-ups (Sosta et al, 2008;Schutte et al, 2010). Additionally, migrants' expectations about healthcare received during pregnancy commonly differ and conflict with the normative procedures of the host country.…”
Section: Introductionmentioning
confidence: 99%